" Scattered Anime Fragments Collected ": Love Poetry and Augustinian Morality in The Secretum and The Canzoniere - Mateo Saldado (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2018)
The issue of poetry's intrinsic value is no stranger to the internal tensions of Petrarch's thought. Although Petrarch defends poetry as a means of accessing Truth, itself the source of moral elevation, vulgar poetry cannot, for him, play the same role. In the third day of the Secretum, he uses an Augustinian moral framework to condemn love poetry. This censure, which appears to be categorical, does not explain why he would continue to compose and organize his Canzoniere until the end of his life. However, by studying the narrative structure of the text and certain compositions which give structure to the collection of poems, a response can be formulated which reconciles these verses with Augustinian morality.